2021
DOI: 10.1186/s12915-021-00990-w
|View full text |Cite
|
Sign up to set email alerts
|

A universal power law for modelling the growth and form of teeth, claws, horns, thorns, beaks, and shells

Abstract: Background A major goal of evolutionary developmental biology is to discover general models and mechanisms that create the phenotypes of organisms. However, universal models of such fundamental growth and form are rare, presumably due to the limited number of physical laws and biological processes that influence growth. One such model is the logarithmic spiral, which has been purported to explain the growth of biological structures such as teeth, claws, horns, and beaks. However, the logarithmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The sum of S τ , S r , and S K , which was defined as the global sensitivity ( S g ) of the component across the three growth phases, showed a similar long-tailed distribution shape. The four distributions were all likely to follow the power law 44, 45 , which agreed well with the ML-predicted conclusion that only a few components determined the growth. This finding strongly suggested that the fate decision components were present among the 41 components, regardless of the complex interactions among these components.…”
Section: Resultssupporting
confidence: 84%
“…The sum of S τ , S r , and S K , which was defined as the global sensitivity ( S g ) of the component across the three growth phases, showed a similar long-tailed distribution shape. The four distributions were all likely to follow the power law 44, 45 , which agreed well with the ML-predicted conclusion that only a few components determined the growth. This finding strongly suggested that the fate decision components were present among the 41 components, regardless of the complex interactions among these components.…”
Section: Resultssupporting
confidence: 84%
“…With that said, it is also important to note that factors beyond functional constraints could influence the patterns of morphospace occupation observed in our results. Teeth can develop into an amazing array of shapes, but conical teeth are still limited in form by developmental constraints that prevent certain extreme areas of morphospace being occupied [58]. Similarly, other factors such as phylogenetic inertia could drive patterns observed in the results.…”
Section: Discussionmentioning
confidence: 99%
“…It implies the tendency towards some adaptive optimum in organismal ‘design’ or, more likely, the presence of one or more constraints that prevent significant and systematic deviation from a common pattern. These constraints may be functional in nature, such as trade-offs that could occur between conflicting requirements of individual muscles in the execution of disparate tasks (see Introduction), or may have a developmental basis ( e.g ., Evans et al, 2021 ). Given the multidimensional and nonlinear aspects of muscle architecture and function, and terrestrial locomotor biomechanics in general, it would be naïve to suggest that a bivariate statistical model such as those derived here can sufficiently represent the mechanical phenomena involved ( Taylor & Thomas, 2014 ).…”
Section: Discussionmentioning
confidence: 99%